Performance of synthetic mammography in the detection of architectural distortion: a comparison with conventional 2D digital mammography - L, Huntrakul; S, Udomphon; P, Kongmebhol; J, Rujiwetpongstorn; M, Mutarak (Biomedical Sciences and Clinical Medicine, 2020)
Objectives To compare the performance of synthetic mammography (SM) and conventional 2D digital mammography (DM) in the detection of architectural distortion (AD). Methods A retrospective review was conducted by three breast imaging radiologists for DM and SM of 33 patients (16 distorted and 17 non-distorted) to identify the presence or absence of and the location of AD. The results were checked for consensus with the standard digital breast tomosynthesis (DBT) reference. STATA version 16.0 was used to analyze the sensitivity, specificity, accuracy, positive predictive value (PPV), and negative predictive value (NPV) of each method. Logistic regression was used to calculate the Area Under the Curve (AUC) and the Chi-squared test was used to compare the AUC between the two methods. Results The sensitivity, specificity, PPV, NPV and accuracy of detection of AD with DM versus SM were 62.5% vs 62.5%, 70.6% vs 88.2%, 66.7% vs 83.3%, 66.7% vs 71.4% and 66.7% vs 75.8%, respectively. The AUC (95% CI) of the SM technique for detection of AD was higher than the DM technique: 0.75 (0.61-0.90) compared with 0.67 (0.50-0.83) (p = 0.32). Conclusion SM provides equal and potentially better diagnostic performance than DM in the detection of AD.